2019
DOI: 10.21037/jtd.2018.11.96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of second primary cancer on the prognosis of patients with non-small cell lung cancer

Abstract: Background: Second primary cancer (SPC) is not a rare event for patients with non-small cell lung cancer (NSCLC), especially for those who survive for a longer period of time. This study was aimed to explore the effects of SPC on the survival of NSLCL patients. Methods: A total of 241,805 patients with primary NSCLC were identified between 2004 and 2014 from the Surveillance, Epidemiology, and End Results (SEER) database. The incidence of SPC and its effect on the overall survival (OS) and lung cancer-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In another study, among patients who underwent resection of stage I non‐small cell lung cancer (NSCLC) of initial primary lung cancer, the incidence of second primary lung cancer has been reported to be 12% 5 . Another recent study also supported the finding that there is a relatively high risk of occurrence of second primary lung cancer among initial primary lung cancer patients 6 . The relatively high incidence of second primary lung cancer is not the only challenge for treatment.…”
Section: Introductionmentioning
confidence: 91%
“…In another study, among patients who underwent resection of stage I non‐small cell lung cancer (NSCLC) of initial primary lung cancer, the incidence of second primary lung cancer has been reported to be 12% 5 . Another recent study also supported the finding that there is a relatively high risk of occurrence of second primary lung cancer among initial primary lung cancer patients 6 . The relatively high incidence of second primary lung cancer is not the only challenge for treatment.…”
Section: Introductionmentioning
confidence: 91%
“…It has also been reported that SPLC was observed in 1.5% of patients with lung cancer in the Surveillance, Epidemiology, and End Results (SEER) database 3 . Patients who have previously undergone surgical resection of initial lung cancer are reported to be at a higher risk of developing SPLC 4 . However, the increase in SPLC patients has brought new challenges and discussions to clinical management, including resectability evaluation, surgical procedure selection, follow‐up advice and prognosis prediction.…”
Section: Introductionmentioning
confidence: 94%
“…3 Patients who have previously undergone surgical resection of initial lung cancer are reported to be at a higher risk of developing SPLC. 4 However, the increase in SPLC patients has brought new challenges and discussions to clinical management, including resectability evaluation, surgical procedure selection, follow-up advice and prognosis prediction. It is inappropriate to treat SPLC as initial primary lung cancer (IPLC), although some similarities between them are shared.…”
Section: Introductionmentioning
confidence: 99%
“…According to research done by Wu and coworkers, the incidence of SPMs among patients with non-small cell lung cancer is about 6.4%. Furthermore, their findings indicated that 50.7% of SPMs occurred during the first year after the diagnosis of non-small cell lung cancer [5]. However, the risk of SPMs following a diagnosis of lung HGNEC remains unclear.…”
Section: Introductionmentioning
confidence: 99%